Prevalence and implications of exercise pulmonary hypertension in chronic thromboembolic pulmonary disease. (3rd October 2022) - Naka, Y; Inami, T; Takeuchi, K; Kikuchi, H; Goda, A; Kohno, T; Soejima, K
Abstract: Introduction: Recent international statement on chronic thromboembolic pulmonary hypertension proposed the definition of chronic thromboembolic pulmonary disease (CTEPD) and advocated further research regarding its clinical characteristic, natural history, and therapeutic strategy. Exercise pulmonary hypertension (Ex-PH) has been considered a mild degree of pulmonary hypertension (PH) among patients with normal pulmonary hemodynamics at rest. However, the clinical significance of Ex-PH in CTEPD remains unknown. Purpose: In the patients with CTEPD, we aimed to verify 1) the prevalence and clinical profiles of Ex-PH, 2) effect of BPA on pulmonary vascular response after exercise in Ex-PH, 3) long-term clinical outcomes of conservative management in non-Ex-PH. Methods: We retrospectively reviewed 26 patients with CTEPD (median age 65 years, 38% male), who underwent cardiopulmonary exercise test with right heart catheterization (CPET-RHC). The definitions of CTEPD are the following 1) pulmonary artery occlusion due to organic thrombus confirmed by imaging studies after ≥3 months of anticoagulation, 2) mPAP<25 mmHg and PAWP≤15 mmHg at rest. PQslope was plotted using multipoint plots. Ex-PH was defined by PQ slope>3.0, and the patients were divided into Ex-PH and non-Ex PH groups. Clinical profiles and long-term outcomes were compared between two groups. The patients in Ex-PH groupunderwent CPET-RHC 6–12 months after balloon pulmonary angioplasty (BPA). In Non-Ex-PH group, serial measurements of echocardiography were performed. Results: Overall, 5 and 21 patients were categorized as CTEPD with PH (mPAP 21–24mmHg) and without PH (mPAP≤20mmHg), and 14 and 12 were categorized Ex-PH and non-Ex-PH groups, respectively. Although all 5 patients with CTEPD with PH were classified as Ex-PH group (Figure 1), there was no significant difference in baseline hemodynamics at rest between Ex-PH and non-Ex-PH groups (mPAP: 19.5 [18.4–20.6] vs. 17.7 [16.6–18.9] mmHg, PVR: 2.2 [1.7–2.7] vs. 2.3 [1.9–2.8] wood units, P>0.05, respectively). PQ slope was significantly higher in Ex-PH group (4.6 [3.2–6.0] vs. 1.31 [0.2–2.8], p=0.002). There were no differences in respiratory function test, blood gas analysis, and 6-minute walk distance between two groups. There were no major adverse events such as all-cause mortality and hospitalization for PH in overall cohort. Among Ex-PH group, BPA decreased PQslope (4.8 [3.6–6.4] to 2.3 [1.9–3.0], p<0.05). Among no-Ex-PH group, there was no significant change in tricuspid regurgitation pressure gradient (28 [17–33] to 27 [21–36] mmHg, p>0.05) over the 997 [651–1451] days. Conclusion: Ex-PH was common in patients with CTEPD, and there were no clinical profiles differentiating Ex-PH from non-Ex-PH, except parameters of CPET-RHC. BPA improved an abnormal pulmonary vascular response to exercise in Ex-PH. The conservative management in non-Ex-PH was feasible. Randomized clinical trials will be needed to further investigate this treatment strategy. Funding Acknowledgement: Type of funding sources: None.